Exploring Political Globalization A Multidisciplinary and Quantitative Analysis of Countries Throughout History (Global Journal of Human-Social Science, 2023)
How many countries are there in the world?" is a question that has so far received little attention as a research topic. The objective of this paper is to explore this issue by developing a conceptual and methodological reflection. It analyzes three key questions: the determination of the number of countries, the definition of a country, and the quantification of the countries of the world. Drawing from the perspectives of various social sciences disciplines, it highlights that researchers put forward contradictory conclusions about the evolution of the number of countries. The problem is that they are lacking appropriate data. The paper presents GeoPolHist, a quantitative database dedicated to the identification of the geopolitical entities of the world over the last two centuries. This new research tool is used to reveal significant changes since 1816: a downward trend in the number of the world's countries and a political restructuring of the world after WWII.
Keywords: database of the world’s countries; geopolitical entity; list of all countries; list of sovereign states since 1816